Estudos estruturais e funcionais da toxina Gi-Tx1 da peçonha da aranha caranguejeira brasileira Grammostola iheringi (MYGALOMORPHAE: Theraphosidae) - Gabriela Gontijo Montandon (2011)
Most of the initial work on spider venoms has been devoted to the study of medically important species. Venoms of apparent lower toxicity, before neglected, have shown increased interest for scientific studies, because they are sources of important biochemical probes for the pharmacological dissection of molecular processes. Tarantulavenoms are rich mixtures of salts, nucleotides, free amino acids, neurotransmitters, polyamines, peptides, proteins and enzymes. Grammostola iheringi is a Brazilian tarantula spider found mainly in southern part of Brazil. Here, we studied the poison fractions and mainly a new toxin of 3.585 Da, named Gi-Tx1. The activities of this toxin werecharacterized by bioassays, electrophysiological screening performed on dorsal root ganglia neurons (DRG) and in voltage-gated sodium and potassium channels subtypes that have been transfected in ovocites of Xenopus leavis. Our results shows that Gi-Tx1 causes a partial block of inward (40%) and outward (20%) currents in DRG cells at 2 M and it is able to block Nav 1.2-.4, 1.6 subtypes, partially blocks Nav1.5 andDmNav, and fully blocks currents from Kv 4.3 subtypes and hERG channels at 2 M. In tumor cells, the toxin was able to reduce the proliferation (specifically on SKHep-1 and MGSO3 cells) but did not affect proliferation rates of normal cells (human PBMC's). These results reveal thepromiscuous action of Gi-Tx1 on ion channels and indicate its possible antiproliferative effects. It would be interesting to verify if exist a correlation of the effects of this toxin in ionic channels and its antitumoral activity.